Exploration of a KI-catalyzed oxidation system for direct construction of bispyrrolidino[2, 3-b]indolines and the total synthesis of (+)-WIN 64821. Issue 1 (3rd December 2019) - Chen, Si-Kai; Yang, Ju-Song; Dai, Kun-Long; Zhang, Fu-Min; Zhang, Xiao-Ming; Tu, Yong-Qiang
Abstract : A facile and environmentally benign KI(cat.)/NaBO3 ·4H2 O oxidation system has been developed for the tandem oxidative aminocyclization/coupling of tryptamines, affording a series of 3 a, 3 a ′-bispyrrolidino[2, 3- b ]indolines with high efficiency (up to 94% yield). Abstract : A facile and environmentally benign KI(cat.)/NaBO3 ·4H2 O oxidation system has been developed for the tandem oxidative aminocyclization/coupling of tryptamines, affording a series of 3 a, 3 a ′-bispyrrolidino[2, 3- b ]indolines with high efficiency (up to 94% yield). This reaction features an electrophilic "I + " mechanism, which is importantly quite different from and milder than the typical radical-involving process, and can be readily amplified for the total synthesis of (+)-WIN 64821.